Enhancement of Thermal Properties of Fluids With Dispersion of Various Types of Hybrid/Nanoparticles. Issue 1 (March 2021) - Rani, Chilaka Vidya; Kumar, Parvesh
Abstract: The main aim of the present research is to enhance the thermal properties of fluids with a dispersion of various types of hybrid/nanoparticles which has the capability of improving heat transfer properties. Thermal conductivities of Nanofluids are probably higher as compared with conventional fluids. The use of metal nanoparticles has not been intensely investigated for heat transfer applications due to a lack of stability. Research hard work has been equally put forth to improve the active performance of heat transfer fluid (HTF) through the use of hybrid nanomaterial. The particularly higher surface-to-volume ratio of nanomaterial makes them properly promote nucleation and heat switch in PCM. The right choice and training of nanomaterials pave the manner for achieving superior thermal conductivity, specific heat, and heat transfer ordinary performance of hybrid nanofluids. Nanomaterials, organized in splendid systems collectively with nanotubes, nanorods, nanoparticles, etc. would possibly display off awesome thermo-bodily factors while dispersed in heat transfer fluid (water). Therefore, various hybrid/nanoparticles have synthesized the usage of the sol-gel approach. Synthesized Nanomaterials are to be tested for XRD, SEM to recognize the crystalline structure, length, form, etc. The ultrasonic process needs to be performed during the dispersion of nanoparticles in HTF for uniform dispersion and to avoid agglomeration. Then nano-based fluids are characterized to study Physical, thermal properties. The nanofluids are tested using Fourier Transformer Infrared Spectrometry (FTIR) to check chemical compatibility between HTF and nanoparticles, later a thermal conductivity analyzer is used to verify thermal conductivity of various hybrid/nano-based fluids. A thermogravimetric analyzer (TGA) is used to check the commencement and end of decomposition temperature of various hybrid/nano-based fluids. Later several experimentations are carried out using shell and tube type heat exchanger to study heat transfer characteristics of various hybrid/nanofluids. The results from various characterization techniques and experimentation are analyzed for optimizing the nanoparticles type and proportions used in HTF for proposing in practical applications.